Decolonisation of Health Sciences curricula as a vehicle for transformation in Higher Education: A scoping review - Koch, R.; Pool, J.; Heymans, Y. (South African Journal of Higher Education, 2025)
Inclusive curriculum transformation is crucial in Higher Education (HE). Decolonisation is considered a necessary intervention that offers opportunities to reimagine curricula, broaden access, and foster inclusivity. However, the full potential of decolonisation remains untapped due to contradictory perceptions and the absence of substantive decolonial theory. This scoping review explored how the decolonisation of Health Sciences curricula can be used as a vehicle for transformation in HE. A systematic search of online academic databases was conducted and included 31 relevant articles. Deductive and inductive coding was used to analyse the data, through which 14 decolonial actions were identified and presented as an action framework. By identifying and organising the main concepts used in the literature and proposing an action framework to decolonise curricula within the field of Health Sciences, this study contributes to the ongoing discourse of how decolonisation can be used to bring about transformation in HE. Contribution: Findings contribute to the development of decolonial theory and highlight the benefits of decolonising Health Sciences curricula. This scoping review sets the stage for further research to build on this action framework, develop practical guidelines to guide curriculum change and evaluate and measure decolonisation efforts.